Beyond Income: Managing Multidimensional Poverty through an Integrative Capability Framework - Hafni Juniyanti; Hulwati; Duhriah (Journal of Principles Management and Business, 2026)
Poverty remains a persistent development challenge that cannot be adequately understood through income-based measures alone, as many households experience simultaneous deprivations in education, health, and living standards. This study examines multidimensional poverty by integrating economic and non-economic perspectives and explores its implications for inclusive development. A qualitative library research approach was employed by synthesizing theories and empirical evidence from peer-reviewed journal articles, academic books, and institutional reports published by organizations such as the United Nations Development Programme (UNDP), the World Bank, and Statistics Indonesia (BPS). The analysis was conducted through literature classification, qualitative content analysis, conceptual synthesis, and interpretation. The findings indicate that multidimensional poverty results from dynamic interactions among income, education, health, and living standards, where deprivation in one dimension reinforces deprivation in others, creating a persistent poverty cycle. Guided by the Capability Approach, the study demonstrates that poverty should be understood as capability deprivation rather than merely insufficient income. The study further proposes an integrative conceptual framework linking multidimensional poverty, capability development, and inclusive development, highlighting that sustainable poverty reduction requires coordinated improvements in economic opportunities, human capital, healthcare, and access to basic services. This framework constitutes the principal contribution of the study by providing a more comprehensive explanation of the mechanisms through which multidimensional deprivation influences inclusive development. The findings offer a conceptual foundation for designing more integrated and sustainable poverty alleviation policies and provide directions for future empirical research.